Carvacrol Induces Candida albicans Apoptosis Associated With Ca2+/Calcineurin Pathway - Niu, Chao; Wang, Chenglu; Yang, Yijia; Chen, Ruiyao; Zhang, Jian; Chen, Haiyan; Zhuge, Yingzhi; Li, Jingqi; Cheng, Jianhua; Xu, Ke; Chu, Maoping; Ren, Chunhua; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
As the prevalence of systemic fungal infections caused by Candida albicans gradually increases, it is necessary to explore potential and effective antifungals. Carvacrol is reported to be lethally toxic to C. albicans, involving several potential mechanisms. However, the form and specific mechanism of cell death caused by this compound has not been delineated. In this study, we found that carvacrol could significantly decrease C. albicans survival rates, consistent with previous researches. Further examination proved that carvacrol treatment caused cell membrane permeability and depolarization. To elucidate the association between cell death and apoptosis, DNA fragmentation and metacaspase activation were determined; as expected, these two apoptosis-related markers were clearly observed. Moreover, total and mitochondrial reactive oxygen species (ROS) levels were elevated, and both mitochondrial transmembrane potential and morphology were disrupted. Additionally, cytosolic and mitochondrial calcium levels were also increased by carvacrol. Calcineurin inhibition experiments revealed cyclosporine A (CsA) addition notably rescued cell growth and inhibited metacaspase activation, indicating that carvacrol triggered C. albicans apoptosis through inducing calcineurin activation. Carvacrol was demonstrated to both have low toxicity and be effective in alleviating systemic infections with C. albicans, which might be via its antifungal and immunomodulation activities. This study suggests that carvacrol has excellent potential as a natural protective compound against C. albicans infections.